New species and new collection records of Prosthetopine water beetles from southern Africa (Coleoptera: Hydraenidae) - Perkins, Philip D. (Zootaxa, 2008)
New species of Hydraenidae are described in the genera Prosthetops Waterhouse (1), Pterosthetops Perkins (1), Parasthetops Perkins & Balfour-Browne (13), and Mesoceration Janssens (24). New collecting locality data are given for the following species described by Perkins & Balfour-Browne (1994): Parasthetops aeneus, P. nigritus, P. spinipes, P. curidius, Mesoceration distinctum, M. rivulare, M. jucundum, M. splendorum, M. rubidum, M. fusciceps, M. languidum, M. dissonum, M. rufescens, and M. brevigranum. High resolution digital images of the holotypes of new species are presented (online version in color), and male genitalia are illustrated. Distribution maps are provided for all prosthetopine species in the genera Prosthetops, Pterosthetops, Parasthetops, and Mesoceration. The following 39 new species are described (type locality in South Africa unless otherwise given): Prosthetops gladiator (Eastern Cape Province, summit of Prentjiesberg); Pterosthetops hawequas (Western Cape Province, Hawaquas radio tower); Parasthetops benefossus(Western Cape Province, Wiedouw farm), P. buunicornus (Lesotho: Drakensberg, Sani Pass Valley), P. confluentus (Eastern Cape Province, Little Karroo, Baviaanskloof N valley), P. lemniscus (Lesotho: Drakensberg, Sani Pass Valley), P. namibiensis (Namibia: Windhoek, Eros Mt.), P. pampinus (Western Cape Province, Dorps River into Prins Albert, Swartbergpas), P. parallelus (Northern Cape Province, Richtersveld, Oemsberg), P. propitius (Lesotho: Drakensberg, Sani Pass Valley), P. retinaculus (Eastern Cape Province, Sundays River system, Letskraal), P. sebastiani (Lesotho: Drakensberg, Sani Pass Valley), P. semiplanus (Eastern Cape Province, Sundays River system, Letskraal), P. striatus (Northern Cape Province, Namaqualand, Kamieskroon), P. unicornus (Eastern Cape Province, Naudes Nek, 12 miles ENE Rhodes); Mesoceration barriotum (Western Cape Province, Cape-Swartberg, Seweweekspoort Kloof), M. bicurvum (Eastern Cape Province, Wildebees River), M. bispinum (KwaZulu-Natal Province, Weza, Impetyene Forest), M. compressum (Eastern Cape Province, S. coast, Dwesa forest reserve), M. concavum (Mpumalanga Province, Blyderiver Canyon), M. curvosum (KwaZulu-Natal Province, Umtamvuna River), M. disjunctum (Eastern Cape Province, Nature's Valley Reserve), M. drakensbergensis (Lesotho, Drakensberg, Sani Pass Valley), M. durabilis (Western Cape Province, 2 miles SW of Citrusdal), M. granulovestum (Western Cape Province, Cederberg, Eikenboom), M. incarinum (Lesotho, Drakensberg, Sani Pass Valley), M. integer (KwaZulu-Natal Province, Busheladi Stream on Lundy's Hill near Deepdale), M. littlekarroo (Western Cape Province, Little Karroo, Rus-en-vredewaterf), M. longipennis (Western Cape Province, W. Wiedouw farm), M. maluti (Lesotho, Drakensberg, Sani Pass Valley), M. natalensis (KwaZulu-Natal Province, Umkomaas River, where crossed by Himeville to Impendhle road), M. periscopum (Western Cape Province, Cederberg, Eikenboom), M. piceum (Western Cape Province, Cederberg, Eikenboom), M. rapidensis (Western Cape Province, S. W. Cape Mts., Hawequas SE), M. repandum (Western Cape Province, Cederberg, Eikenboom), M. reticulatum (Western Cape Province, Nuweberg Forest Station), M. semicarinulum (Western Cape Province, Groot Toren farm), M. tabulare (Western Cape Province, Platteklip Gorge, north face of Table Mountain), M. umbrosum (Western Cape Province, Wiedouw farm).